Pulmonary hypertension leads to poor inpatient outcome in non-white patients admitted with stroke: an analysis of national inpatient sample - Jayaraman, Dilip Kumar; Kjelstrom, Stephanie; Montone, Georgia; Rajasekaran, Divya (Frontiers in Stroke, 2024)
Stroke is one of the leading causes of death and disability worldwide. Every year, about 795,000 strokes are reported, of which around 23% are recurrent. We analyzed the national inpatient sample to assess the patient outcomes in patient with pulmonary hypertension and ischemic stroke. Our study included 7 million inpatient discharge encounters among which 553,085 patients had ischemic stroke. Among this, 16,830 had PH and 536,255 did not have PH.female (63.8% vs. 48.8%; p<.0001). A higher proportion of stroke patients with PH died in the hospital (5.7% vs. 3.7%; p<.0001) as well as had a longer average LOS (6.3 days (SD 6.2) vs. 5.0 days (SD 6.8); p<.0001).Our study noted that black patients with PH were the youngest (70.5 yrs. (SD 13.8). Black patients had the longest (7.8 days SD 8.3) (p<.0001).